Integrating green marketing with halal Principles: Impact on consumer behavior, market dynamics, and brand strategy - Fauzi, Nurul; Husna, Nawal; Alim, Hidayat Nur; Hidayati, Nurul; Casim, Rashdi M. (Halal Studies and Society, 2024)
This study aimed to thoroughly explore the manner in which green marketing can be incorporated alongside halal principles to influence consumer behavior, market dynamics, and brand positioning. Generally, green marketing emphasizes sustainability, transparency, innovation, and consumer engagement, while halal principles ensure compliance with Islamic Sharia standards. The convergence of these methods has been observed to typically address the increasing demand for products that are both environmentally and ethically compliant. For instance, brands such as Kiva and Zalal Foods have successfully adopted effective integration strategies to ensure the production of eco-friendly halal-certified products, which, in return, enhanced brand reputation and consumer trust. During the course of this study, challenges associated with the integration of green marketing and halal principles, including stricter material selection and dual certification processes, were also discussed. The results showed that integrating green marketing and halal principles led to the development of a unique value proposition, allowing brands to meet evolving consumer preferences and positioning each producer as a leader in sustainable and ethical markets. This integration was observed to be particularly essential for expanding market share, fostering brand loyalty, and addressing growing awareness of social and environmental responsibilities among global consumers.